3D biomechanical analysis of the preparation of the long jump take off - Panoutsakopoulos, V. M; Papaiakovou, G. I.; Katsikas, F. S.; Kollias, I. A. (New Studies in Athletics, 2010)
The purpose of the present study was to describe the 3D kinematics of the long jump approach and take-off and their effect upon the flight and the landing.